3D reconstitution and numerical analysis of superelastic behavior of porous shape memory alloy. (15th August 2019) - Zhu, Shijie; Bouby, Céline; Cherouat, Abel; Ben Zineb, Tarak
Highlights: A 3D foam microstructure is built on the basis of the ellipsoid cell unit pores with random dimension, position and orientation using MATLAB-ABAQUS. Constitutive equations of superelastic behavior are used to simulate the compression of porous shape memory alloys. The effects of porosity, size, ratio of long axis and short axis, orientation and distribution of closed and open cells foams are significant on the effective stiffness, the forces in the start and the finish of forward and reverse transformation (between Austenite and Martensite) and the dissipation energy decrease. The mechanical analysis from the microstructure of porous SMA material provide us a better understanding of this kind of structure, which is used for the design of some specified devices demanding the advantage of porous SMA. Abstract: In this work, a CAD 3D foam structure of Ni-Ti Shape Memory Alloy (SMA) is rebuilt using ellipsoid unit cells in order to study the superelastic behavior of porous SMAs. A taking and placing algorithm based on a uniform and a normal distributions is adopted for the 3D reconstitution process. In the design sample, dimensions, positions and orientations of the ellipsoid unit cells are randomly selected. A SMA constitutive model including phase transformation, martensitic reorientation and twins accommodation is selected to simulate the superelastic behavior of the SMA foam. As an application, the compression of SMA porous sample with random ellipsoid unit cell distribution is simulated by finite element in order to show the efficiency of the proposed methodology to predict its superelastic response and to analyze the porosity effect. The obtained results show that the force-displacement or stress-strain responses of the porous material are highly depend on the foam porosity. The effects of porosity, size, orientation, ratio of long axis and short axis, and distribution of unit cell on the superelastic behavior of SMA porous material are also discussed in both closed cells and open cells cases.